(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2014)
The MEP status is based in the immunity and the representative mandate. The legal framework. Shows a complex enviroment of powers and rights. However it invites us to theme about an inproved conexion between votes and elected.